HYDROLATES AND ESSENTIAL OILS AFFECT Varroa destructor MITES IN in vitro ASSAYS - Ríos-Argüelles, Noe; Islas-Medina, Ivan; Aguilar-Ambrocio, Gigi Margot; Montes-Maldonado, Rafael; Soto Simental, Sergio; Ayala-Martinez, Maricela (Chilean Journal of Agricultural & Animal Sciences, 2025)
The beekeeping industry is affected by infestation of hives by Varroa destructor mites, reducing both honey yield and quality. The objective of this study was to evaluate the effects of hydrolates or essential oils on the survival of V. destructor mites using in vitro assays. Six hydrolates obtained from Lavandula angustifolia, Tithonia diversifolia, Ruta graveolens, Dalbergia palo-escrito, Populus alba, and Retama sphaerocarpa, as well as two essential oils from Lavandula angustifolia and Origanum vulgare were used. Behavioral changes and survival rates were evaluated to determine the effects of hydrolates or plant-based essential oils on V. destructor mites. Results indicate that essential oils of L. angustifolia and O. vulgare at low concentration (1.25 µL), as well as the hydrolate obtained from the flowers of Retama sphaerocarpa are effective against V. destructor without compromising bee survival. In conclusion, essential oils and hydrolates may serve as alternative treatments to reduce V. destructor mite infestations, particularly R. sphaerocarpa flower and T. diversifolia hydrolates, and 4 µL of O. vulgare essential oil.